2015
DOI: 10.1097/bot.0000000000000297
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Talar Neck Fractures

Abstract: The overall rate of osteonecrosis was 0.312. Rates for Hawkins' types I-IV were 0.098, 0.274, 0.534, and 0.480, respectively. The mean rate of subtalar arthritis was 0.49 but increased to 0.81 in studies with >2 years of follow-up. Complication rates are high in talar neck fractures, and patients should be counseled accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 29 publications
2
37
0
1
Order By: Relevance
“…Despite several decades have passed, with inherent progress in surgical techniques, equipment and management of soft tissue injuries, the rate of post-traumatic ON is still considerable, as proven by the data emerged from the present review, which focused on clinical trials published in the last 30 years. Anyway, a recent meta-analysis has suggested that surgical managament of talar fractures, which became routine only after 1990, has contributed to reduce the rate of ON, especially in Hawkins II and III neck fractures [30]. Surprisingly, the present review found a large variability among studies regarding the incidence of post-traumatic ON, with some trials reporting values as low as 10% and others presenting higher incidence, up to 50% of cases.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Despite several decades have passed, with inherent progress in surgical techniques, equipment and management of soft tissue injuries, the rate of post-traumatic ON is still considerable, as proven by the data emerged from the present review, which focused on clinical trials published in the last 30 years. Anyway, a recent meta-analysis has suggested that surgical managament of talar fractures, which became routine only after 1990, has contributed to reduce the rate of ON, especially in Hawkins II and III neck fractures [30]. Surprisingly, the present review found a large variability among studies regarding the incidence of post-traumatic ON, with some trials reporting values as low as 10% and others presenting higher incidence, up to 50% of cases.…”
Section: Discussionmentioning
confidence: 54%
“…There is no clear evidence whether a fixation technique (screws vs plate vs K wires) is better than the other, nor if there are surgical tricks (e.g. screws placed anterior to posterior rather than posterior to anterior) that could improve clinical outcome [30]. Similarly, the use of a double surgical approach does not seem to increase the risk of ON with respect to the single access [10].…”
Section: Discussionmentioning
confidence: 99%
“…The second most common complication is subtalar arthritis. [4] Elgafy et al reported an association of 53.3 percent subtalar arthritis and 25 percent tibiotalar arthritis with talus fractures. [5] Failure to prevent these complications will lead to chronic pain, disability, and multiple surgeries.…”
Section: Introductionmentioning
confidence: 98%
“…The most dreaded complication of talar neck fracture is osteonecrosis of the body of talus which ultimately leads to collapse of the body. Subtalar arthritis is the 2nd most common complication observed following a talar neck fracture [ 4 ]. The complications can be as high as 53.3% with subtalar arthritis and 25% with tibiotalar arthritis as reported by Elgafy et al [ 5 ].…”
Section: Introductionmentioning
confidence: 99%